AID in Chronic Lymphocytic Leukemia: Induction and Action During Disease Progression - Oppezzo, Pablo; Navarrete, Marcelo; Chiorazzi, Nicholas (Frontiers in Oncology, 2021)
The enzyme activation-induced cytidine deaminase (AID) initiates somatic hypermutation (SHM) and class switch recombination (CSR) of immunoglobulin (Ig) genes, critical actions for an effective adaptive immune response. However, in addition to the benefits generated by its physiological roles, AID is an etiological factor for the development of human and murine leukemias and lymphomas. This review highlights the pathological role of AID and the consequences of its actions on the development, progression and therapeutic refractoriness of chronic lymphocytic leukemia (CLL) as a model disease for mature lymphoid malignancies. First, we summarize pertinent aspects of the expression and function of AID in normal B lymphocytes. Then we assess putative causes for AID expression in leukemic cells emphasizing the role of an activated microenvironment. Thirdly, we discuss the role of AID in lymphomagenesis, in light of recent data obtained by NGS analyses on the genomic landscape of leukemia and lymphomas, concentrating on the frequency of AID signatures in these cancers and correlating previously described tumor-gene drivers with the presence of AID off-target mutations. Finally, we discuss how these changes could affect tumor suppressor and proto-oncogene targets and how they could be associated with disease progression. Collectively, we hope that these sections will help to better understand the complex paradox between the physiological role of AID in adaptive immunity and its potential causative activity in B-cell malignancies.